Ambitious and driven to scale the barriers to top management: experiences of women leaders in the Nigerian technology sector. (27th June 2022) - Odoh, Anne; Branney, Peter
Abstract: The four theories—gendering of careers, glass ceiling, gender stereotypes and work-life balance—of the lack of inclusion of women in the technology sector have a certain face validity when looking at Nigeria, a historically patriarchal nation undergoing significant growth in penetration and diffusion in the technology sector. Consequently, this article is the first to further develop these theories through a critical realist exploration of the experiences of female senior managers in the Nigerian technology sector. The findings show that women technology leaders are ambitious and driven to scale the barriers to senior management roles. These four theories are extended by providing empirical data and insights into how this phenomenon is experienced differently in the Global South. The article recommends that organizations implement policies that support skilled and high-potential women employees to fulfill their career aspirations, thereby disrupting stereotypes and changing the dominant, masculine narrative of the technology industry.